Ответ:
В решении.
Объяснение:
1) -36ad - (3a - 6d)² = a = √3; d = √7;
= -36ad - (9a² - 36ad + 36d²) =
= -36ad - 9a² + 36ad - 36d² =
= -9a² - 36d² =
= -9 * (√3)² - 36 * (√7)² =
= -9 * 3 - 36 * 7 =
= -27 - 252 = -279.
2) Тождественное выражение: -9a² - 36d².
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
В решении.
Объяснение:
1) -36ad - (3a - 6d)² = a = √3; d = √7;
= -36ad - (9a² - 36ad + 36d²) =
= -36ad - 9a² + 36ad - 36d² =
= -9a² - 36d² =
= -9 * (√3)² - 36 * (√7)² =
= -9 * 3 - 36 * 7 =
= -27 - 252 = -279.
2) Тождественное выражение: -9a² - 36d².